Application of Word Folding Board Media for Improvement of Word Vocabulary Students with Intellectual Disabilities - Nuryani, Nunung (JASSI ANAKKU, 2021)
The purpose of this study was to examine the level of effectiveness of using word folding board media to increase intellectual disability students’ vocabulary mastery. The subjects of this research were 4 intellectual disability students. The research method used was a classroom action-type method with a participatory collaborative type, with a demonstration learning method carried out in 2 cycles. The data used in this study was field studies through observation and learning outcomes tests. The results of data analysis showed that there is an increase in the vocabulary of intellectual disability students as much as 30-40% which is seen from the comparison of the initial test to the final test for 2 cycles, which is also indicated by an increase in the value of Indonesian lessons, with the grades 78,80,75,81. It was above the Minimum Completeness Criteria value of 70. This letter folding board media is a fairly new and interesting medium, with elements of guessing games that are still attached to the elements of playing and interesting pictures. This media encourages students to try using this media to increase vocabulary in Indonesian language lessons. This study demonstrates that the use of interesting and easy-to-use media will accelerate understanding and increase vocabulary in students, especially intellectual disability students. In addition, it also challenges teachers to improve their media modification skills so that it is easier to guide their students.